Space weathering induced via microparticle impacts: 2. dust impact simulation and meteorite target analysis - Fiege, Katherina; Guglielmino, Massimo; Trieloff, Mario (Journal of geophysical research. Planets, 2019)
The role of micrometeorite bombardment in space weathering on asteroid surfaces was studied using a 2 MV Van de Graaff accelerator. About 90,000- to 100,000-micron- to submicron-sized copper particles with a mass and velocity distribution similar to the interplanetary dust population were fired onto the surfaces of polished Allende CV3 chondrite and eucrite NWA 6966 samples at speeds between 1 to 70 kilometers per second. We find a clear relationship between microparticle bombardment, infrared reflectance decrease, and overall spectral reddening. Differences in impact effects due to variable particle speed, size, and structure are observed. Some Cu particles form large clusters that break up upon impact and disperse. Other impactors leave imprints on the surface, and implant or generate typical craters with rims and spallation features. Very small, fast particles generate small craters without spallation or significant crater rim. Mid-infrared (IR) spectra (bulk and microscopic measurements of individual components), 3-D laser microscopic images and XRD spectra from the processed and unprocessed samples were collected. Mid-IR spectra (700-6,000 cm−1) over the entire sample surface show overall darkening of features. Microscopic IR spectra show the damage seen as reflectance decrease and spectral reddening, which is variable in the micrometer range, depending on impact density and target properties (mineralogic composition). The fine-grained Allende matrix with predominantly Fe-rich olivine seems less affected than coarse-grained chondrules with Mg-rich silicates, where darkening can reach 60%. X-ray diffraction analysis also suggests chemical and crystallographical differences in the bombarded sample, due to impact shock.